Association of Apelin and Apelin Receptor Polymorphisms With the Risk of Comorbid Depression and Anxiety in Coronary Heart Disease Patients - Wang, Ying; Liu, Wenhui; Xiao, Yiwen; Yuan, Haiyan; Wang, Feng; Jiang, Pei; Luo, Zhiying (Frontiers in Genetics, 2020)
The Apelin (APLN)/apelin receptor (APLNR) signaling pathway is a newly identified regulator in various cardiovascular diseases, which is considered as a candidate pathway for the occurrence of coronary heart disease (CHD), depression, and anxiety. The goal of this study was to investigate the association between APLN/APLNR gene polymorphisms and the risk of depression and anxiety in CHD patients. To this end, a case-control study involving 269 CHD patients and 184 healthy control individuals was conducted. The 269 patients with CHD including 122 patients with and 147 patients without depression, and 56 patients with and 213 patients without anxiety Four single nucleotide polymorphisms were selected and successfully genotyped using Sanger sequencing. The APLN rs2235310T allele and APLNR rs9943582C allele were found to be associated with an increased risk of CHD after multiple test correction (P-adjust < 0.05). The patients with CHD who carried the rs9943582C allele had a higher risk of depression, after adjusting for alcohol drinking habits, insomnia, hypertension, and stroke history, with the Bonferroni correction (P-adjust = 0.018). The APLNR rs2282623 T allele was associated with an increased risk of anxiety in CHD patients after adjusting for related disease complications, with the Bonferroni correction (P-adjust = 0.022). We reported for the first time that the APLN rs2235310 and APLNR rs2282623 polymorphisms are associated with the risks of psychiatric disorders in CHD patients and may serve as novel biomarkers for therapy.